Association of adverse pregnancy outcome and domestic/intimate partner violence - Jagtap, Vijyeta R.; Samant, Padmaja Y. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Domestic/intimate partner violence is not a mere household issue. It is a global phenomenon that occurs in all the countries and cuts across all strata, races and countries. Apart from being an issue of human/individual rights, it also has major health consequences. The main aim of this study is to stress the need of screening and detecting violence in antenatal women. Methods: This was a questionnaire based observational cross sectional study done at King Edward Memorial Hospital, Mumbai, India over a span of one year. A total of 200 antenatal/postnatal patients seeking healthcare were enrolled after an informed consent with approval from the Institutional Ethics Committee. Percentages of various parameters were analysed. Test of significance was Chi square test and Odd’s ratio (p <0.05). Results: Prevalence of domestic/intimate partner violence in our study was 12.5% and 7% in the group with normal pregnancy outcome and 18% in group with adverse pregnancy outcome. It was found that violence was more prevalent in age group of 21 to 30 years, love marriages, nuclear families, lower educational level of partner, addiction in partner, unplanned pregnancies, lower economic conditions and families supporting dowry and gender bias and allowing freedom of choice and contraception. Conclusions: Need for routine screening for violence in women of reproductive age group with vulnerable subset of pregnant women. Creating awareness/sensitivity amongst healthcare professionals and to train them to identify and help these women.